Attentional blink in children with attention deficit hyperactivity disorder - Amador-Campos,Juan A. (2015)
Objective:To explore the temporal mechanism of attention in children with attention deficit hyperactivity disorder (ADHD) and controls using a rapid serial visual presentation (RSVP) task in which two letters (T1 and T2) were presented in close temporal proximity among distractors (attentional blink [AB]).Method:Thirty children aged between 9 and 13 years (12 with ADHD combined type and 18 controls) took part in the study. Both groups performed two kinds of RSVP task. In the single task, participants simply had to identify a target letter (T1), whereas in the dual task, they had to identify a target letter (T1) and a probe letter (T2).Results:The ADHD and control groups were equivalent in their single-task performance. However, in the dual-task condition, there were significant between-group differences in the rate of detection of the probe letter (T2) at lag + 1 and lag + 4. The ADHD group exhibited a larger overall AB compared with controls.Conclusion:Our findings provide support for a link between ADHD and attentional blink.